Pemanfaatan Platform Digital dalam Meningkatkan Mutu Pendidikan - Yusra; Sesmiarni, Zulfani (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to analyze the utilization of digital platforms to improve the quality of education at SMAN 1 Candung. Using a qualitative approach and descriptive methods, this research explores how teachers and students leverage digital technology in the learning process while identifying factors that support or hinder its effectiveness. Digital platforms such as Google Classroom and Zoom have proven to enhance the flexibility and efficiency of learning, enabling more inclusive teaching and encouraging independent learning among students. However, this study also identifies challenges, including limited internet access, insufficient technological facilities, and varying levels of digital literacy among teachers and students. The findings reveal that digital literacy levels at SMAN 1 Candung vary significantly. While some teachers possess basic knowledge of technology use, they require further training to maximize the potential of digital platforms. On the other hand, students are more familiar with social media but struggle to distinguish valid and relevant information. This disparity in digital literacy is exacerbated by infrastructure limitations, which hinder accessibility and the optimal use of technology in learning. The study also highlights the importance of blended learning strategies to maintain student engagement while leveraging the benefits of both online and face-to-face learning. With intensive training for teachers, technology usage guidelines for students, and adequate infrastructure support, the potential of digital platforms can be optimized to significantly enhance educational quality in the digital era. This research offers both practical and theoretical contributions to the development of digital-based education, particularly in areas with infrastructure constraints like SMAN 1 Candung, and serves as a model for similar educational institutions in Indonesia.